5-Fluorouracil: A Narrative Review on the Role of Regulatory Mechanisms in Driving Resistance to This Chemotherapeutic Agent - Ghafouri-Fard, Soudeh; Abak, Atefe; Tondro Anamag, Farhad; Shoorei, Hamed; Fattahi, Faranak; Javadinia, Seyed Alireza; Basiri, Abbas; Taheri, Mohammad (Frontiers in Oncology, 2021)
5-fluorouracil (5-FU) is among the mostly administrated chemotherapeutic agents for a wide variety of neoplasms. Non-coding RNAs have a central impact on the determination of the response of patients to 5-FU. These transcripts via modulation of cancer-related pathways, cell apoptosis, autophagy, epithelia-mesenchymal transition, and other aspects of cell behavior can affect cell response to 5-FU. Modulation of expression levels of microRNAs or long non-coding RNAs may be a suitable approach to sensitize tumor cells to 5-FU treatment via modulating multiple biological signaling pathways such as Hippo/YAP, Wnt/β-catenin, Hedgehog, NF-kB, and Notch cascades. Moreover, there is an increasing interest in targeting these transcripts in various kinds of cancers that are treated by 5-FU. In the present article, we provide a review of the function of non-coding transcripts in the modulation of response of neoplastic cells to 5-FU.